2019
DOI: 10.3389/fnins.2019.01225
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Repetitive Transcranial Magnetic Stimulation Mediates Autophagy Flux in Human Bone Mesenchymal Stromal Cells via NMDA Receptor–Ca2+–Extracellular Signal-Regulated Kinase–Mammalian Target of Rapamycin Signaling

Abstract: Wang et al. rTMS-Mediated Autophagy Flux Conclusion: In the 0.5 T group, high-frequency rTMS can induce autophagy through NMDAR-Ca 2+-ERK-mTOR signaling in BMSCs. In the 1.0 and 1.5 T groups, autophagy is not activated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Many researches claimed that magnetic force and stimulation might increase growth factor secretion after nerve injury. 37,38 In this study, we similarly noted that some neural marker levels were upregulated, and the findings indicated that remyelination The sufficient regeneration of nerves and end plate organs requires adequate supply of nutrients, primarily from surrounding vessels and intraneural microvessels. We also evaluated some vascular markers, such as vascular endothelial growth factor (VEGF) and CD34.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Many researches claimed that magnetic force and stimulation might increase growth factor secretion after nerve injury. 37,38 In this study, we similarly noted that some neural marker levels were upregulated, and the findings indicated that remyelination The sufficient regeneration of nerves and end plate organs requires adequate supply of nutrients, primarily from surrounding vessels and intraneural microvessels. We also evaluated some vascular markers, such as vascular endothelial growth factor (VEGF) and CD34.…”
supporting
confidence: 59%
“…The results strengthened previous findings that intrinsic magnetized nanoparticle scaffolds could promote extension of the neurofilament and outgrowth of the axons in the middle parts for regeneration (Figure f–h). Many researches claimed that magnetic force and stimulation might increase growth factor secretion after nerve injury. , In this study, we similarly noted that some neural marker levels were upregulated, and the findings indicated that remyelination and axonal regeneration were efficiently improved by the implantation of magnetized scaffolds in the defected nerve area.…”
supporting
confidence: 55%
“…mTOR Signaling: The mammalian target of the rapamycin (mTOR) pathway is involved in regulating protein synthesis and cellular homeostasis. TMS has been associated with changes in mTOR signaling [ 79 ]. Inflammatory pathways: TMS-induced changes in neural activity may have downstream effects on inflammatory pathways involving cytokines and microglial activation [ 80 ].…”
Section: Basic Theory Of Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…In a rat model, HF-rTMS applied during the acute and subacute phase of cerebral ischemia inhibited apoptosis by significantly enhancing the expression of Bcl-2 and reducing the expression of Bax compared to controls [ 149 , 150 ]. The use of c-TBS was reported to have an inhibitory effect on the activation of caspase-3 and caspase-9 [ 20 ], while rTMS can increase the ratio of LC3-II/I and decrease p62 through NMDAR–Ca 2+ –mTOR signaling [ 151 ]. Although this TMS effect can be important for poststroke recovery, it is not completely clear if this potentially augmented autophagy of TMS is eliciting a beneficial effect through clearance of the postischemic debris rather than prevention of neuronal death.…”
Section: Transcranial Magnetic Stimulation—short Introductionmentioning
confidence: 99%